Activation of Most Toll-Like Receptors in Whole Human Blood Attenuates Platelet Deposition on Collagen under Flow - Y. Liu; S. L. Diamond (Journal of Immunology Research)
Platelets have toll-like receptors (TLRs); however, their function in thrombosis or hemostasis under flow conditions is not fully known. Thrombin-inhibited anticoagulated whole blood was treated with various TLR agonists and then perfused over fibrillar collagen using microfluidic assay at venous wall shear rate (100 s-1). Platelet deposition was imaged with fluorescent anti-CD61. For perfusion of whole blood without TLR agonist addition, platelets rapidly accumulated on collagen and eventually occluded the microchannels. Interestingly, most of the tested TLR agonists (Pam3CKS4, MALP-2, polyinosinic-polycytidylic acid HMW, imiquimod, and CpG oligodeoxynucleotides) strongly reduced platelet deposition on collagen, while only the TLR4 agonist endotoxin lipopolysaccharide (LPS) enhanced deposition. Following 90 sec of deposition under flow of untreated blood, the addition of various TLR-7 agonists (imiquimod, vesatolimod, and GSK2245035) all caused immediate blockade of further platelet deposition. Since TLR signaling can activate nuclear factor-kappaB (NF-κB), the IKK-inhibitor (IKK inhibitor VII) and NF-κB inhibitor (Bay 11-7082) were tested. The IKK/NF-κB inhibitors strongly inhibited platelet deposition under flow. Furthermore, addition of Pam3CSK4 (TLR1/2 ligand), MALP-2 (TLR2/6 ligand), and Imquimod (TLR7 ligand) reduced phosphotidylserine (PS) exposure. Activation of TLR1/2, TLR2/6, TLR3, TLR7, and TLR9 in whole blood reduced platelet deposition under flow on collagen; however, LPS (major Gram negative bacterial pathogenic component) activation of LTR4 was clearly prothrombotic.